Revision of Pyramidellidae (Gastropoda: Heterobranchia) from Argentina triples their diversity in northern Patagonia. (20th December 2018) - Güller, Marina; Zelaya, Diego G
Abstract: During an intensive sampling of the molluscan fauna from San Matías Gulf, northern Patagonia, Pyramidellidae were the most diverse family and one of the most abundant. This is in contrast with previous literature, in which only seven species have been mentioned from the area. Here we revise the species collected in this area and, in the light of this information, provide a reassessment of the diversity of this group in Argentina. We recognize 24 pyramidellid species, belonging to the genera Boonea, Fargoa, Peristichia, Careliopsis, Turbonilla, Eulimastoma, Ondina and Odostomia s. l. New distributional ranges for Peristichia lepta, Careliopsis bahiensis, Turbonilla farinatiae, T. zulmae, T. rushii, Eulimastoma franklini and Odostomia puelchana are given. A neotype is designated for Turbonilla sanmatiensis . The status of the type material of T. uruguayensis and Boonea multituberculata is clarified, and the latter species is redescribed and figured. In addition, nine new species are described, five of them comprising specimens that had previously been misidentified. The presence of eight other species, previously regarded as distributed from the Caribbean or Floridean Provinces to Argentina is here questioned. As a result of this study, a total of 28 valid species of pyramidellids are currently recognized from Argentina.